The girl with no reflection - Chow, Keshe (Delacorte Press, 2024)
Selected by the royal matchmaker to marry the crown prince, Ying Yue finds her husband-to-be stoic and infuriating, leading her to escape into a secret parallel world through palace mirrors where a kinder prince awaits, but the two worlds have a long and bloody history and Ying has a part to play in the future of both.